Analysis of flow and heat transfer in a new lattice. (January 2015) - Xiao, Hongguang; Yang, Lei; Yan, Binghuo
Highlights: A new lattice with plum blossoms shape and non-uniform wall thickness is proposed. The flow and heat transfer in the new lattice are analyzed with URANS approach. The new lattice is superior to the traditional lattice when 0 < e / D ⩽ 0.06. The frictional resistance coefficient and Nu have maximum values when e / D = 0.03. Abstract: The turbulent flow and heat transfer in a new lattice with non-uniform wall thickness are simulated and discussed by Unsteady Reynolds-Averaged Navier–Stokes (URANS) method with the Reynolds Stress Model (RSM). The simulation results agree well with the experimental data. It is shown that this new lattice with plum blossoms shape is propitious to the reasonable distributions of velocity and temperature as compared with the lattice with uniform wall thickness within a certain spanwise angle ( θ ). The amplitude of transverse oscillation velocity monotonically increases with the increase of thickening height ( e / D ), and the frequency first increases and then decreases. The frictional resistance coefficient and Nusselt number will reach their peak values when e / D = 0.03. The lattice with plum blossoms shape and non-uniform wall thickness is superior to the traditional lattice when 0 < e / D ⩽ 0.06 and inferior to the traditional lattice when 0.06 < e / D < 0.12.